2022
DOI: 10.3389/fnins.2022.897226
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Baseline for Human Cortical Folding Morphological Variables: A Multisite Study

Abstract: Differences in the way human cerebral cortices fold have been correlated to health, disease, development, and aging. However, to obtain a deeper understanding of the mechanisms that generate such differences, it is useful to derive one's morphometric variables from the first principles. This study explores one such set of variables that arise naturally from a model for universal self-similar cortical folding that was validated on comparative neuroanatomical data. We aim to establish a baseline for these variab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…We control for sex in all of the reported analyses (also see the supplement for an analysis controlling head size with comparable results). Fourthly, the magnitude of longitudinal changes in gyrification during the relatively short follow-up period in our study is modest, but within the range of lifespan, changes were observed among healthy subjects in larger studies 73 , 74 . Our careful exclusion of movement-related confounds, the application of longitudinal image registration, and the use of the same scanning parameters over a relatively short time (months) reduced measurement inaccuracy, thus strengthening our interpretation.…”
Section: Discussionmentioning
confidence: 47%
“…We control for sex in all of the reported analyses (also see the supplement for an analysis controlling head size with comparable results). Fourthly, the magnitude of longitudinal changes in gyrification during the relatively short follow-up period in our study is modest, but within the range of lifespan, changes were observed among healthy subjects in larger studies 73 , 74 . Our careful exclusion of movement-related confounds, the application of longitudinal image registration, and the use of the same scanning parameters over a relatively short time (months) reduced measurement inaccuracy, thus strengthening our interpretation.…”
Section: Discussionmentioning
confidence: 47%
“…Performing the PCA in the human harmonized dataset [1, 3, 9, 19, 25, 30, 40, 41], one obtain the results summarized in Figure 1. We analyzed separately subjects in the 20-40 yo age range, who presumably have a fully developed cortex (in broad terms, after development but before significant aging), and subjects in the age range between 20-60 years, for whom age effects were mathematically removed (henceforth “de-aged”) [3]. Table 1 summarizes the differences between the principal components and the theoretical expectation.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid this problem, we used two techniques: (i) restrict the analysis to the age range between 20-40 years (adulthood) as it would be the best representation of a stationary fully developed cortex; (ii) take advantage of the harmonization linear regression, removing the age dependence using each subject age and the angular coefficient fitted, a procedure called here deageing. The latter allows to perform the analysis to the full age range (20-60 years) in which the model was experimentally validated [3]. In Appendix 5, one finds the replication of the analysis for all age ranges on the dataset (with and without the deageing).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations